The Scoring of Early Classical Concertos 1750-1780 - Maunder, Richard 1937-2018 (Woodbridge Boydell, 2014)
In the baroque era most concertos were - in the modern sense of the term - chamber music, to be played by a small group of musicians each reading from an individual printed or manuscript part. Indeed, composers often expected the soloist to be accompanied by just a string quartet with a harpsichord or organ continuo. But over the thirty years from 1750, as the classical style was being developed, numbers began to rise slowly. This did not happen at a uniform rate throughout Europe, however, for many concertos continued to be played one-to-a-part, and even by 1780 an ensemble with more than eight or nine strings would have been unusual. The nineteenth-century notion that a concerto pitted a lone soloist against a full symphony orchestra still lay some years in the future.At the same time ideas about form were changing, as the Vivaldian ritornello pattern metamorphosed into the concerto-sonata form used by Mozart and his contemporaries; some unconventional variants appeared as composers strove to keep abreast of latest developments. It was a fascinating period of innovation, in which many hundreds of concertos were written. To be sure, not all of them can be described as "forgotten masterpieces", but among them there are some very fine works that certainly ought to be revived. It is hoped that readers of this book may be encouraged to explore this comparatively neglected repertoire.RICHARD MAUNDER is a Fellow of Christ's College, Cambridge. His previous book, The Scoring of Baroque Concertos, was published by The Boydell Press in 2004. He has also published books on Mozart's Requiem, Keyboard Instruments in Eighteenth-Century Vienna and numerous editions of seventeenth- and eighteenth-century music.
Keywords: 18th Century (1701-1800); Concerto; Orchestration